Partial Characterization of Extracellular α-Amylase from Three Bacillus Isolates (Bangladesh Journal of Microbiology, 2010)
α-Amylase produced by three Bacillus isolates had been compared on the basis of the following criteria: heat and pH effects on activity and stability, effect of metal ions on enzyme activity and kinetic parameters. The culture filtrates obtained by growing the organisms in starch medium were fractionated by ammonium sulphate precipitation technique, and the highest enzyme activities were recovered from 70% saturation fraction. The enzyme from Bacillus amyloliquefaciens showed optimum activity at 60°C, while B. subtilis and another Bacillus isolate at lower (55°C) temperature. The pH optima of the enzymes from all sources were between 6.5 and 7.0 with an optimum reaction time of 10 to 15 min. α-Amylases were moderately thermostable exhibiting almost full activities at 50°C for at least 20 min. The enzyme from all sources showed stability over a wide range of pH (4.0-8.5). The apparent Km values on soluble starch varied between 1.6 mg/ml in case of B. amyloliquefaciens and 2.5 mg/ml in case of B. subtilis. Metal ions like Mg2+ and Mn2+ seemed to have positive influence on the enzyme activities of B. subtilis and Bacillus sp. The enzyme activities from three isolates were strongly inhibited by Cu2+, Hg2+ and Zn2+. Key words: Extracellular α-amylase; Bacillus spp.; Enzyme characterizationDOI: http://dx.doi.org/10.3329/bjm.v25i1.4864 Bangladesh J Microbiol, Volume 25, Number 1, June 2008, pp 76-78